A study on organic pollution based on algal distribution in some rural and Temple ponds of Balrampur, U.P. India - S.P.M. Tripathi; Madhavi Pathak; J. P. Tiwari (Environment Conservation Journal, 2008)
The present  paper  deals  with  the  algal  distribution  and  organic  pollution  in  fifteen  rural  and  temple  ponds in   Balrampur.   Algae   belonging   to   Chlorophyceae,   Cyanophyceae,    Euglenophyceae   and   Bacillariophyceae were studied.  Occurrence  of  Microcystis aeruginosa  was  observed in  many ponds.  Among the  ponds studied  one pond  showed  confirm  high  organic  pollution,  five  ponds  moderate   organic   pollution,   five   probable   high organic pollution and  four ponds no organic pollution.